Haemosporidian parasites of a European passerine wintering in South Asia: diversity, mixed infections and effect on host condition - Synek, P; Albrecht, T; Vinkler, M; Schnitzer, J; Votýpka, J; Munclinger, P (Parasitology research, 2013)
We studied haemosporidian parasites in the scarlet rosefinch Carpodacus erythrinus in a small isolated semicolony during an eight-year period using molecular methods of parasite detection. The scarlet rosefinch is an interesting model of parasite host species. It winters in South Asia which represents a rare exception among European passerines. Males express yellow to red carotenoid-based plumage ornament which is a good predictor of male reproductive success. In 240 blood samples originating from 199 adult individuals, the total parasite prevalence reached 60%. Prevalence varied among years from 36 to 81% in Haemoproteus, 8 to 22% in Plasmodium, and 0 to 14% in Leucocytozoon. Twenty parasite lineages were detected (Haemoproteus: 5 lineages, Plasmodium: 10 lineages, and Leucocytozoon: 5 lineages). Among them, the Haemoproteus ROFI2 lineage, which is a host-specific parasite lineage of the scarlet rosefinch, was the most frequently found. Parasite lineages showed varying degree of lineage specificity. While Haemoproteus lineages detected in the scarlet rosefinch have relatively narrow host breadth restricted mainly to Fringillidae family, Leucocytozoon and Plasmodium lineages generally showed wider host range. The presence of some parasite lineages hitherto detected in sedentary European passerines (SISKIN1, CCF3, BT2) or in Culicoides biting midges at the same locality (ROFI1) suggest local transmission. On the contrary, lineages LK05 and FANTAIL1 that were previously reported exclusively from Asian hosts imply parasite transmission at the scarlet rosefinch wintering sites in South Asia. Mixed infections were found in 17% of infected samples and comprised mainly the most frequent lineages. The pattern of concomitant infections seemed to be rather random and matched expected levels based on lineage frequencies. Between-year comparisons revealed that in a majority of the repeatedly captured individual hosts the infection status remained unchanged (individuals stayed uninfected or possessed the same parasite lineages). However, 16 gains and 8 losses of lineages were also reported. We have not found any effect of haemosporidians on male carotenoid ornament expression or host body mass.
Keywords: Male; Asia; Haemosporida; Europe; prevalence; Asie; mužské pohlaví; Coinfection; protozoální infekce zvířat; nemoci ptáků; Evropa; Blood; Animals; Protozoan Infections, Animal; zvířata; Bird Diseases; Prevalence; koinfekce; Passeriformes; krev